Faculty development for health professions education: mandatory and indispensable - Cintra, Karine Angélica; Bollela, Valdes Roberto (Revista brasileira de educação médica, 2025)
ABSTRACT Introduction: Faculty development programs (FD) are activities aimed at improving the competencies required of educators. They involve topics related to curriculum design, teaching-learning, student and program evaluation, research, management and leadership of educational processes. In Brazil, after the publication of the curricular guidelines for medical education in 2014, it is mandatory for educational institutions to create and maintain FD programs in undergraduate medical programs. Development: Brazilian institutions of higher education have begun to structure their FD centers to meet the legislation and, obviously, to support teachers and preceptors responsible for the training of doctors in Brazil. The way in which these initiatives have been evolving is still very diverse, random, and not always with evaluation of the quality and effectiveness of these actions. This essay approaches the FD topic from the global context, and advances with an analysis of how the issue has been developed in Brazil, from the perception and experience of the authors. The scientific production on the subject at the national level is incipient and we believe that the production of knowledge in the area is a priority for the coming years, since Brazil is among the countries with the largest number of medical schools worldwide. Looking at the international experience is fundamental, but insufficient since the Brazilian context of medical schools and the health system itself is unique and needs to be understood and considered regarding FD actions. Final considerations: The evaluation of the quality and effectiveness of FD programs in health professions education is fundamental for the improvement of teaching and health care, which ultimately must ensure patient safety and sustainability of the health system itself. RESUMO Introdução: Programas de desenvolvimento docente (DD) são atividades voltadas ao aprimoramento das competências requeridas de educadores. Envolvem temas ligados ao desenho de currículos, ao ensino-aprendizagem, à avaliação do estudante e de programas, à produção de conhecimento (pesquisa) e à gestão e liderança de processos educacionais. No Brasil, após a regulamentação das diretrizes curriculares para a graduação em Medicina em 2014, existe uma obrigatoriedade para que as instituições de ensino criem e mantenham programas de DD nos cursos de graduação em Medicina. Desenvolvimento: As instituições brasileiras de ensino superior começaram a estruturar seus centros de DD para atender à legislação e, obviamente, para apoiar professores e preceptores responsáveis pela formação de médicos no Brasil e dar suporte a eles. A forma como essas iniciativas vêm evoluindo ainda é muito diversa, aleatória e nem sempre com avaliação da qualidade e efetividade das ações. Este ensaio aborda o tema DD a partir do contexto mundial e avança com uma análise sobre como a questão tem sido trabalhada no Brasil, a partir da percepção e experiência dos autores. A produção científica sobre o tema em nível nacional é incipiente, e acreditamos que a produção de conhecimento na área seja uma prioridade para os próximos anos, visto que o Brasil figura entre os países com maior número de escolas médicas no mundo. O olhar para a experiência internacional é fundamental, mas insuficiente, visto que o contexto brasileiro das escolas médicas e do próprio sistema de saúde é único e precisa ser compreendido e levado em conta nas ações de DD. Conclusão: A avaliação da qualidade e efetividade dos programas de DD em instituições de ensino da saúde é fundamental para a melhoria do ensino e do cuidado em saúde que, em última instância, deve garantir segurança ao paciente e sustentabilidade do próprio sistema de saúde.